A Review on the Electroless Deposition of Functional Materials in Ionic Liquids for Batteries and Catalysis - Lahiri, Abhishek; Pulletikurthi, Giridhar; Endres, Frank (Frontiers in Chemistry, 2019)
Developing functional materials via electroless deposition without the need of external energy is a fascinating concept. Electroless deposition can be subcategorized into galvanic displacement reaction, disproportionation reaction and deposition in presence of reducing agents. Galvanic displacement reaction is a spontaneous reduction process wherein the redox potentials of the metal/metal ion in the electrolyte govern the thermodynamic feasibility of the process. In aqueous solutions, the galvanic displacement reaction takes place according to the redox potentials of the standard electrochemical series. In comparison, in the case of ionic liquids, galvanic displacement reaction can be triggered by forming metal ion complexes with the anions of the ionic liquids. Therefore, the redox potentials in ILs can be different to those of metal complexes in aqueous solutions. In this review, we highlight the progress in electroless deposition of metals and semiconductors nanostructures from ionic liquids and their application towards lithium/sodium batteries and in catalysis.